ANALISIS PENINGKATAN KASUS KERACUNAN MAKANAN DI INDONESIA DAN URGENSI PENGETATAN SANKSI HUKUM TERHADAP PELAKU USAHA PANGAN - Frency Siska; Roni Sahindra; Hermansyah Caniago; Afnilaswati (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2026)
The increasing number of food poisoning cases in Indonesia in recent years reflects the weakness in food safety supervision and the low compliance of food business operators with health and safety standards. This study aims to analyze the factors contributing to the rise in food poisoning cases in Indonesia and examine the urgency of tightening legal sanctions against food business operators who violate food safety regulations. This research uses a normative juridical approach with library research methods, analyzing laws, scientific literature, and data on food poisoning cases published by relevant agencies. The findings indicate that the rise in food poisoning cases is influenced by weak supervision of food distribution, the use of hazardous substances, low hygiene awareness among food operators, and the inadequate enforcement of food safety laws. Furthermore, the current legal sanctions are considered ineffective in deterring violations, as they are still administrative and relatively lenient compared to the health risks posed to the public. Therefore, tightening legal sanctions through stronger regulations, improved coordinated supervision, and the imposition of stricter penalties and criminal sanctions against food business operators that endanger consumers is necessary. This study is expected to contribute academically and provide policy recommendations to strengthen the consumer protection and food safety system in Indonesia.